DAKWAH PENGENTASAN KEMISKINAN; QUR??ANIC SOCIAL-ENGINEERING - Muhammad Nashrul Haqqi (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2014)
Abstract This paper highlighted the empowerment of the community as the goal preaching. Preaching in this context was no longer technocratic, but participatory, were preaching in accordance with the conditions, changes and needs, including problems solving in society such as poverty. As an epistemology of preaching, the Qur'an was a guide for the preachers. But often the preachers were unable to reveal the values of the Qur'an that was supposed to be a solution to society's problems. This paper departed from 9 terms in the Qur'an about poverty, namely: miski>n, faqr, ba>??is, ??ailah, imla>q, mahru>m, sa>??il, qa>ni?? and mu'tar. In the process of uncovering the Qur??an view related to the poverty, it was revealed that the Qur'an further highlight about poverty elimination from the perspective of an outsider or apart with the poor, although the responsibility was also on people with poverty itself. Based on the analysis of the various terms, it was revealed that many solutions such as infaq, sadaqah, zakat, fa??i and ghanimah which no longer could be understood as religious orders that could not be contextualized in modern management and institutionalization. Keyword: al-Qur??an, poverty, solution, social-engineering Tulisan ini menyoroti pemberdayaan masyarakat sebagai muara dari dakwah. Dakwah dalam konteks ini tidak lagi teknokratis, melainkan partisipatif, yaitu dakwah yang sesuai dengan kondisi, perubahan dan kebutuhan, termasuk memecahkan problem dalam masyarakat seperti kemiskinan. Sebagai epistemologi dakwah, al-Qur??an adalah panduan bagi para pelaku dakwah. Namun seringkali para pelaku dakwah itu tidak mempu menguak nilai-nilai Qur??ani yang seharusnya menjadi solusi persoalan masyarakat. Tulisan ini berangkat dari 9 terma dalam al-Qur??an tentang kemiskinan, yaitu: miski>n, faqr, ba>??is, ??ailah, imla>q, mahru>m, sa>??il, qa>ni?? dan mu??tar. Dalam proses mengungkap pandangan Qur??ani terkait dengan kemiskinan, terungkap bahwa al-Qur??an lebih menonjolkan pengentasan kemiskinan dari sudut pandang outsider atau selain penyandang kemiskinan, meskipun tanggungjawab tersebut juga berada pada penyandang kemiskinan itu sendiri. Berdasarkan analisa, terungkap bahwa solusi pengentasan kemiskinan seperti infaq, sadaqah, zakat, fa??i dan ghanimah tidak lagi bisa dipahami sebagai perintah agama yang tidak dapat dikontekstualisasikan dalam pengelolaan dan pelembagaan modern. Kata kunci: al-Qur??an, kemiskinan, solusi, rekayasa-sosial.